Constructions of United States government development funding in response to the global gag rule - Molobela, Reabetswe Lee-Anne (Rhodes University, Faculty of Humanities, Department of Psychology, 2020)
Despite South Africa's progressive abortion law, barriers to safe abortion are numerous and exist at both the macro and micro level. Barriers include abortion stigma, discrimination, strong moral judgements against abortion within society and conscientious objection among health care workers. Furthermore, women's lack of knowledge regarding the legal status of abortion and the voluminous illegal advertisements of back street abortions undermines the legislation and promotes unsafe abortions. Sexual and reproductive health rights (SRHR) non-governmental organizations (NGOs) have served as a link between service and people by providing information about safe abortion to women, especially in rural areas and have received funding from various platforms including United States government. However, the United States government has established the global gag rule which forbids foreign non-governmental organizations receiving United States government funding from using United States government and non-United States funds for abortion related activities. The global gag rule has been reinstated and extended by the current United States president. As such the global gag rule is expected to have an adverse effect on sexual and reproductive health rights in South Africa and on Sexual and reproductive health rights non-governmental organizations. The aim of the study is to highlight the constructions and responses to the global gag rule by sexual and reproductive health rights non-government organization workers in the South African context. This study used semi-structured individual interviews to collect data through purposive and snowball sampling of 10 South African Sexual and reproductive health rights non-governmental organizations workers. The study is situated within the social constructionist framework with emphasis on Fairclough's three aspects of the constructive effects of discourse as an analytic tool in conjunction with Braun and Clarke's social constructionist thematic analysis. The results of the study reflect on participants' construction of United States government as imposing conservative agendas and taking regressive steps towards Sexual and reproductive health rights, which have in turn invoked indirect and direct resistance from non-governmental organizations. Additionally, NGO workers have constructed subject positions that highlight the vulnerability of non-governmental organizations dependency on United States government 1funding as it destabilizes and fragments civil society organization while it compromises the effectiveness of non-governmental organizations in serving the needs of intended communities. United States government is also constructed as strengthening abortion stigma and strengthening barriers to safe abortion that already exist in the country.
Keywords: Pro-choice movement -- South Africa; Abortion -- Law and legislation -- South Africa; Abortion -- Moral and ethical aspects -- South Africa; Abortion -- Psychological aspects; Reproductive rights -- South Africa; Economic assistance, American -- South Africa; Non-governmental organizations -- South Africa; Discourse analysis; Social constructionism; Global Gag Rule